GAMBARAN KEPERCAYAAN DIRI PENDERITA SKOLIOSIS DENGAN PENGGUNAAN SCOLIOSIS BRACE - Nur Rachmat (Politeknik Kementerian Kesehatan Banjarmasin, 2019)
ABSTRACT : The purpose is to return to the normal contour and align the spine and then makes the feeling of self-confidence sufferers re-arise. This research used quantitative research. The research method used in this study is research carried out with intrinsic case studies, the case taken are interesting cases to study. The research approach is purely qualitative by using direct contact methods, namely interviews. This study focused on the image of the patient's self-confidence using scoliosis.The results of the measurement with scoliosis can be seen from the degree asymmetry stem indicated on the cob angle. From the result of observation that the use of scoliosis brace can be seen, the patient has decreased self-confidence due to the pressure present on the scoliosis brace and the sound produced by the device. Keywords: Self-confidence, Scoliosis, Scoliosis Brace